Caring for the dead in ancient Israel - Sonia, Kerry M. (Archaeology and biblical studies, 2020)
"In Caring for the Dead in Ancient Israel, Kerry M. Sonia examines the commemoration and care for the dead in ancient Israel against the broader cultural backdrop of West Asia. This cult of dead kin, referred to as ancestor cult in some previous studies, in ancient West Asia comprised a range of ritual practices in which the living provided food and drink offerings, constructed commemorative monuments, invoked the names of the dead, and protected their remains"--